Upaya Meningkatkan Pemahaman Keagamaan Masyarakat melalui Program Pendidikan dan Sosial Keagamaan di Desa Alatengae Kabupaten Maros - Eka Syahriani; Awal Rifai (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Alatengae is a village located in the Bantimurung sub-district, Maros district. Alatengae in Indonesian means towards goodness. The purpose of Real Work Lecture (KKN) III STIBA Makassar in Alatengae Village is to realize community service programs which are one of the pillars of the Tri Dharma of Higher Education. The method of implementing community service (PkM) begins with a field survey armed with an independent instrument. The results of the KKN trip show how important this program is, where students (i) and the community have experienced tremendous benefits after the implementation of this activity. Social activities, trainings and teaching were carried out well and smoothly.